Post cardiac surgery home-monitoring system - Georghiou, Georgios P.; Kyriacou, Efthyvoulos C.; Chimonidou, Panayiota; Pattichis, Constantinos S.; Barberis, Vassilis I. I.; Lambrinou, Ekaterini (My University, 2010)
One of the major factors limiting but also causing the application of modern technology in medicine is the response time to patients, should they need specialized medical care. In this work we propose a solution that is aiming to help and improve the patients' life after a cardiac surgery. This is a group of patients that have to be monitored for a short period after the operation. The aim of this project is to give the opportunity to these patients to be monitored at home after their operation so as to keep their rehabilitation period as smooth as possible and avoid unnecessary visits to the hospital or prevent adverse events. This is going to be achieved by creating an integrated web- based system which can regularly monitor several biosignals like ECG, blood pressure, arterial SpO2 and parameters like body weight and provide the tools to identify any unusual events. 2011 ICST Institute for Computer Science, Social Informatics and Telecommunications Engineering.
Keywords: Biosignals monitoring; Cardiac surgery patients; Home monitoring; Web based telemedicine systems